Amphetamines in child medicine: a review of ClinicalTrials.gov - Alalalmeh, Samer O.; Hegazi, Omar E.; Shahwan, Moyad; Alshehri, Fahad S.; Ashour, Ahmed M.; Algarni, Alanood S.; Alorfi, Nasser M. (Frontiers in Pharmacology, 2023)
Background: Globally, the use of amphetamines as therapeutic agents in pediatric medicine is a crucial area of concern, especially given the population's vulnerability.Methods: On August 6, 2023, a search was conducted on ClinicalTrials.gov using "amphetamine" as the keyword. Two independent assessors screened trials against set criteria, including a focus on amphetamine, completion status, an interventional approach, and included children. Ongoing or observational studies were excluded. Data extracted from the qualified trials encompassed primary objectives, participant counts, study duration, and outcomes, with the aim of analyzing human disorders induced by amphetamine.Results: On August 6, 2023, a search of the ClinicalTrials.gov database with the term "amphetamines" identified 179 clinical trials. After rigorous exclusion criteria, 20 trials were ultimately selected for analysis. The predominant condition under investigation was attention deficit hyperactivity disorder (ADHD), present in 84.2% of studies. Key study characteristics included: phase 4 trials (36.8%), randomized allocation (63.2%), and the parallel intervention model (42.1%). Masking techniques varied, with no masking in 42.1% of studies, and double and quadruple masking both accounting for 21.1%. Geographically, 78.9% of the studies' participants were from the United States.This study highlights the notable therapeutic potential of amphetamines in pediatric ADHD populations and emphasizes the importance of recognizing potential side effects and addiction risks. As pharmacogenomics offers the prospect of personalized treatments, there is potential to increase therapeutic efficacy and decrease adverse reactions. It is vital to balance these benefits against the inherent risks, underscoring the need for continued research to optimize the use of amphetamines in medicine.